Using arts-based research to understand the sociocultural facets of having invisible disabilities in a normative society. (1st March 2020) - Allen, Alexandra
AbstractDisability studies is centred around the idea that disability is a social construction. Within the field of disability studies, however, many people with non-apparent disabilities are still underrepresented when it comes to the investigation of how social factors influence the formation of their own disability identity. Throughout this study, I use arts-based research to explore moments of critical disability awareness that highlight instances in which sociocultural factors have influenced my disability identity. By examining certain facets of critical disability studies that address issues of ableism, I am able to emphasize the ways in which critical autobiography can contribute to the discourse of having invisible disabilities within a normative society.